2008
DOI: 10.1002/jcb.21709
|View full text |Cite
|
Sign up to set email alerts
|

APT102, a novel adpase, cooperates with aspirin to disrupt bone metastasis in mice

Abstract: Platelets contribute to the development of metastasis, the most common cause of mortality in cancer patients, but the precise role that anti-platelet drugs play in cancer treatment is not defined. Metastatic tumor cells can produce platelet aIIbb3 activators, such as ADP and thromboxane A2 (TXA2). Inhibitors of platelet b3 integrins decrease bone metastases in mice but are associated with significant bleeding. We examined the role of a novel soluble apyrase/ ADPase, APT102, and an inhibitor of TXA2 synthesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…Interestingly, a population-based epidemiological study reported that the use of platelet inhibitors aspirin and dipyridamole was associated with increased risk of osteoporotic fractures, but this association was not observed with clopidogrel (73). Clinical studies evaluating the effects on bone in patients receiving clopidogrel or trials of clopidogrel in patients with excessive bone resorption are warranted to determine whether clopidogrel or other novel ADP and P2RY12-targeted therapies (11,67,74) could have a role as in the treatment of disease states characterized by excessive bone resorption. We propose that P2RY12 targeting would likely only have effects on bone during localized increases in extracellular ADP that can occur during tissue damage, inflammation, and cancer, with little effects on normal systemic bone turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a population-based epidemiological study reported that the use of platelet inhibitors aspirin and dipyridamole was associated with increased risk of osteoporotic fractures, but this association was not observed with clopidogrel (73). Clinical studies evaluating the effects on bone in patients receiving clopidogrel or trials of clopidogrel in patients with excessive bone resorption are warranted to determine whether clopidogrel or other novel ADP and P2RY12-targeted therapies (11,67,74) could have a role as in the treatment of disease states characterized by excessive bone resorption. We propose that P2RY12 targeting would likely only have effects on bone during localized increases in extracellular ADP that can occur during tissue damage, inflammation, and cancer, with little effects on normal systemic bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that purinergic signaling can modulate platelet function, inflammation, and pathologic angiogenesis, which could modulate bone cell function in certain disease states (2,22,36,(65)(66)(67)(68). Recent preclinical data is conflicting regarding the role of clopidogrel in inflammation both dependently and independently of its effects on platelets (36,68).…”
Section: Methodsmentioning
confidence: 99%
“…Weilbaecher and colleagues investigated the effect of the soluble ADPase APT102 administered in combination with an inhibitor of TXA2 synthesis (acetylsalicylic acid/aspirin). 58 Although ATP102 and aspirin treatment did not affect primary tumor growth, the combined treatment significantly attenuated the extent of melanoma and breast cancer bone metastasis in mice. 58 …”
Section: Platelets and Bone Metastasismentioning
confidence: 96%
“…58 Although ATP102 and aspirin treatment did not affect primary tumor growth, the combined treatment significantly attenuated the extent of melanoma and breast cancer bone metastasis in mice. 58 …”
Section: Platelets and Bone Metastasismentioning
confidence: 96%
“…Early work also highlighted that ATP was useful for purging residual tumour cells in autologous bone marrow transplantation [451]. Furthermore, APT102, a novel form of human apyrase/ADPase, works together with aspirin to disrupt bone metastasis in mice [452]. It is conceivable that ATP released from tumour cells could further stimulate osteoclast formation and activity [12], thus contributing to the so-called vicious cycle of bone destruction that commonly occurs around tumour metastases.…”
Section: Bone Cancer and Multiple Myelomamentioning
confidence: 99%